A CONTRASTIVE AND ERROR ANALYSIS OF ENGLISH EXPRESSIONS - Mutia Putri; Abdillah Surya Dirgantara; Dinda Sabda Aulia; M. Kevin Al-farizy; Audy Serina Nahda; Nuri Handayani; Siti Ismahani (STKIP Subang, 2026)
This study investigates grammatical errors found in English expressions produced by Indonesian learners and corrected by Mr. John on Instagram through the combined perspectives of Contrastive Analysis (CA) and Error Analysis (EA). The study aims to identify the types of grammatical errors, classify them, and explain their underlying causes. Employing a qualitative descriptive design, the research analyzed fifteen authentic English expressions collected from Mr. John's Instagram account (@mr.johnhid). The data were examined by identifying error categories and determining whether they resulted from interlingual transfer or intralingual transfer. The findings reveal that Indonesian learners frequently experience difficulties in verb complementation, prepositions, auxiliary verbs, capitalization, punctuation, subject–verb agreement, copula usage, noun formation, lexical collocation, and word order. Verb complementation errors emerged as the most dominant category (26.7%), followed by preposition errors (20%), while auxiliary verb errors and mechanical errors each accounted for 13.3% of the total data. The analysis indicates that these errors are primarily influenced by structural differences between Indonesian and English as well as learners' overgeneralization of English grammatical rules. The study also demonstrates that Instagram provides authentic learner language data that can enrich linguistic research and support English language teaching. The integration of Contrastive Analysis and Error Analysis offers a comprehensive framework for understanding grammatical difficulties experienced by Indonesian EFL learners in digital communication contexts.